2017
DOI: 10.4314/bcse.v31i2.8
|View full text |Cite
|
Sign up to set email alerts
|

Natural pigment sensitized solar cells based on ZnO-TiO2-Fe2O3 nanocomposite in quasi-solid state electrolyte system

Abstract: ABSTRACT. Nanocomposites of Zn-Ti-Fe oxide using zinc as a host with different ratios of precursor salts were prepared by co-precipitation method to use as semiconductors for dye sensitized solar cell (DSSC). The assynthesized nanocomposites were characterized using XRD, SEM-EDX, TEM and UV-Vis spectrophotometer. DSSCs based on the new semiconductors and di-tetrabutylammoniumcis-bis(isothiocyanato)bis(2,2'-bipyridyl-4,4'-dicarboxylato)-ruthenium(II) (N719) dye has been constructed and characterized. Stability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The amount of each metal in the three different composites is in good agreement with the theoretical composition. where, k is constant (about 0.9), λ is the wavelength (0.15405 nm), β is the full width at half maximum (FWHM) of the diffraction line and θ is the diffraction angle [15]. From the XRD data ( Table 2) we see that the as-prepared sample is nanosized.…”
Section: Elemental Compositionmentioning
confidence: 95%
“…The amount of each metal in the three different composites is in good agreement with the theoretical composition. where, k is constant (about 0.9), λ is the wavelength (0.15405 nm), β is the full width at half maximum (FWHM) of the diffraction line and θ is the diffraction angle [15]. From the XRD data ( Table 2) we see that the as-prepared sample is nanosized.…”
Section: Elemental Compositionmentioning
confidence: 95%
“…The corresponding V OC values for the grape-TiO 2 , orange- 28 Journal of Nanomaterials TiO 2 , and pineapple-TiO 2 photoelectrodes were found to be 0.628, 0.626, and 0.576 mV, respectively. Moreover, reports show that ZnO-TiO 2 -Fe 2 O 3 nanocomposites were synthesized and used as an alternative photoelectrode in the presence of ethanol-extracted Guizotia scabra and Salvia leucanta flower sensitizers [130]. It has been found that the obtained conversion for the ethanol extracts of Guizotia scabra and Salvia leucantha were estimated at 0.0013% and 0.0017%, respectively.…”
Section: Performance Characterizationmentioning
confidence: 99%
“…Copper oxide nanomaterials have been developed substantially in recent years due to its low cost fabrication and good electrochemical properties. Copper oxides NPs are used for gas sensors [4], photovoltaic solar cell [5,6], photo electrochemical cell [7,8] and electro-chromic coatings [9].…”
Section: Introductionmentioning
confidence: 99%